2009
DOI: 10.1177/156482650903000403
|View full text |Cite
|
Sign up to set email alerts
|

Ironin VitroBioavailability and Iodine Storage Stability in Double-Fortified Salt

Abstract: These findings were corroborated by field tests in southern India which demonstrated that double-fortified salt containing microencapsulated ferrous fumarate was effective in reducing the prevalence of iron-deficiency anemia and iodine-deficiency disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…This performance is similar to that of capsules produced via agglomeration and extrusion, which also resulted in a ~75% iron dissolution in 30 min. and a ~80% iron dissolution in 2h (Li et al 2009). When ingested with other foods, the premix is expected to perform even better as the presence of other food material has been shown to increase the dissolution and subsequent absorption of iron (Crichton, 2001).…”
Section: Bioavailabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…This performance is similar to that of capsules produced via agglomeration and extrusion, which also resulted in a ~75% iron dissolution in 30 min. and a ~80% iron dissolution in 2h (Li et al 2009). When ingested with other foods, the premix is expected to perform even better as the presence of other food material has been shown to increase the dissolution and subsequent absorption of iron (Crichton, 2001).…”
Section: Bioavailabilitymentioning
confidence: 94%
“…Every 15 min., 5mL samples were withdrawn, filtered (0.45m membrane filter) and analyzed for iron (Li et al, 2009). …”
Section: In-vitro Bioavailabilitymentioning
confidence: 99%
“…The process described by Li, Diosady, and Wesley () and Yadava et al. () was modified for iron premix processing at the last stage of encapsulation.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…The stability, acceptability, and bioavailability of different types of DFS have been analyzed (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Overall, all types of DFS have been found to be acceptable to consumers, and laboratory studies conducted have indicated good stability and bioavailability of both iron and iodine.…”
Section: Introductionmentioning
confidence: 99%